Visual performance and patient satisfaction of multifocal contact lenses in eyes undergoing monofocal intraocular Lens implantation. Issue 3 (June 2020) - Kamiya, Kazutaka; Fujimura, Fusako; Ando, Wakako; Iijima, Kei; Shoji, Nobuyuki
Graphical abstract: Abstract: Purpose: To assess visual performance and patient satisfaction of multifocal contact lenses in eyes having monofocal intraocular lens (IOL) implantation. Methods: We prospectively assessed uncorrected visual acuity at all distances (0.3, 0.4, 0.5, 0.7, 1, and 5 m), higher-order aberrations (HOAs), objective scattering index (OSI), contrast sensitivity, and patient satisfaction, before and during multifocal contact lenses wear in IOL-implanted eyes. Results: Visual acuity at 0.3, 0.4, 0.5, 0.7, 1, and 5 m during wearing multifocal contact lenses was 0.21 ± 0.08, 0.11 ± 0.06, 0.01 ± 0.08, -0.02 ± 0.10, -0.02 ± 0.08, and -0.01 ± 0.07, respectively. We found a significant improvement at near to intermediate distances (30, 40, and 50 cm), but no significant change at intermediate to far distances (70 cm, 1 m, and 5 m). Log contrast sensitivity significantly decreased at 6 and 12 cycles/degrees, but did not significantly change at 1.5, 3, and 18 cycles/degrees. Third-order aberrations significantly increased after CL treatment, but fourth-order aberrations or total higher-order aberrations did not significantly change during CL treatment. The OSI and log(s) did not significantly change during CL treatment. The patient satisfaction score for overall vision significantly improved during CL treatment. Conclusions: Multifocal contact lenses significantly improved visual acuity at near to intermediate distances, and subsequent patient satisfaction, even though contrast sensitivity function slightly decreased, suggesting its viability of presbyopic correction in monofocal IOL-implanted eyes.